Comparison of the Composition of Cinnamomum verum J. Presl and Zingiber officinale Roscoe to the IC50 Value - Aries K. Sundoro; Etty Sulistyowati (Universitas Tadulako, 2022)
Antioxidants are substances that can reduce and prevent free radical damage or prevent oxidative damage. The combination of two or more plant species can result in a greater potential for antioxidant activity. The purpose of this study was to determine the IC50 value of the combination of Cinnamomum verum J. Presl and Zingiber officinale Roscoe with a ratio of 1:2, 1:1, and 2:1. Antioxidant activity was determined by the amount of DPPH absorption inhibition (% Inhibition) and the value (50% Inhibition Concentration). The IC50 value in antioxidant activity measurement of ethanol extract combination of Cinnamomum verum J. Presl and Zingiber officinale Roscoe in the ratio of 1:2, 1:1, and 2:1, was 372.3078 ppm, 354,3077 ppm, and 344.0863 ppm respectively. The ethanol extract of Cinnamomum verum J. Presl and Zingiber officinale Roscoe at a ratio of 2:1 was the best combination with total phenolic content of 5.63 mgGAE/100 g and produced an IC50 value of 344.0863 ppm.